(untitled) (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2026)
This case study examines the strategic reconceptualization of digital marketing by Zomato, India’s leading food delivery platform, during its transformation from a restaurant discovery service to a comprehensive food-tech ecosystem. The study analyzes how Zomato successfully navigated multiple strategic challenges including intense competition, the COVID-19 pandemic, and its transition to a public company, through innovative digital marketing strategies. Using secondary research methodology, this case investigates Zomato’s evolution from 2008 to 2024, focusing on key strategic decisions, digital marketing innovations, and business model transformations. The findings reveal that Zomato’s success stemmed from its ability to reconceptualize digital marketing around emotional engagement, data-driven personalization, and omnichannel integration while maintaining agility during crisis periods. The case provides insights for digital transformation strategies in competitive markets and demonstrates the critical role of timely marketing reconceptualization in sustaining market leadership.